Breastfeeding premature babies: characterization of the mother-child binomial and maternal self-efficacy - Lopes, Antonia Mauryane (2015)
Objective: To analyse breastfeeding in premature babies, relating the characteristics of the mother-child binomial and maternal self-efficacy. Methods: Cross-sectional, descriptive, and exploratory study, with quantitative approach, in a public maternity hospital in the state of Piauí, Brazil, with 21 mothers and their children admitted to a Neonatal Intermediate Care Unit. A questionnaire on the maternal characterization, a checklist for assessment of the breastfeeding technique, and the Breastfeeding Self-Efficacy Scale – Short Form were applied. Results: Of the mothers, 10 (47.6%) were teenagers, 11 (52.4%) single, 10 (47.6%) with low education level, 10 (47.6%) with low income, 12 (57%) had no employment bond, 15 (71.4%) resided in the countryside of the state, 13 (61.9%) had a caesarean section, 11 (52.4%) had a previous pregnancy, 12 (57.1%) were multiparous, 11 (52.4%) had experience in breastfeeding, 12 (57.1%) planned the pregnancy, 16 (72.5%) had prenatal care with less than six visits, without any diagnosis of diseases, and 13 (81.3%) did not receive guidance about breastfeeding. Regarding the newborns, 18 (85.7%) weighed less than 1,500 kg at birth, 10 (47.6%) were fed with mixed/partial maternal breastfeeding, 16 (76.2%) had already used the orogastric feeding tube, 8 (66.7%) had latch difficulties, 7 (58.3%) poor suction, 8 (66.7%) disorganized swallowing, 10 (83.3%) reduced alertness, 9 (75.5%) had short length of feeding, 8 (66.6%) with improper positioning, and 13 (61.9%) had high efficacy in breastfeeding. Conclusion: The mothers showed high efficacy in breastfeeding their premature children. Considering the breastfeeding technique, however, this one was ineffective. doi: 10.5020/18061230.2015.p32